W 75. Rocznicę "Krwawej Niedzieli". Przyczyny i zasięg banderowskiego ludobójstwa dokonanego na obywatelach Drugiej Rzeczypospolitej = Nn the 75th anniversary of "Bloody Sunday". Causes and range of the bandera genocide committed against the citizens of the Second Polish Republic - Isakowicz-Zaleski, Tadeusz (1956-2024) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Volhynian Slaughter of 1943 is a part of the genocide of Poles, as well Polish citizens of other nationalities, which was committed in the period from 1939 to 1947, also in the following provinces: Lviv Province, Stanisławow Province, Tarnopol Province, Lublin Province and Polesie Province. The perpetrators were members of the Organization of Ukrainian Nationalists, which conducted terrorist activities against the Polish state between World War I and World War II.
Keywords: Volhynian Slaughter; "Bloody Sunday"; Ukrainian Insurgent Army; Greek Catholic Church; Ukrainian nationalism; Wołyń; ludobójstwo; "Krwawa Niedziela"; Ukraińska Powstańcza Armia; Organizacja Ukraińskich Nacjonalistów; kościół greckokatolicki; nacjonalizm ukraiński